Platelet-Vesicles-Encapsulated RSL-3 Enable Anti-Angiogenesis and Induce Ferroptosis to Inhibit Pancreatic Cancer Progress - Zhang, Yiyin; Huang, Zhengze; Cheng, Jiaxi; Pan, Haoqi; Lin, Tianyu; Shen, Xuqiu; Chen, Wenchao; Chen, Qi; Gu, Chenhui; Mao, Qijiang; Liang, Yuelong (Frontiers in Endocrinology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most malignant cancers. It is characterized by stromal richness, lack of blood supply and special metabolic reprogramming in the tumor microenvironment, which is difficult to treat and easy to metastase. Great efforts have been made to develop new drugs which can pass through the stroma and are more effective than traditional chemotherapeutics, such as ferroptosis inducers–Erastin and RSL-3. As current anti-angiogenic therapy drugs alone are suboptimal for PDAC, novel vascular disruption agents in combination with ferroptosis inducers might provide a possible solution. Here, we designed human platelet vesicles (PVs) to camouflage RSL-3 to enhance drug uptake rate by tumor cells and circulation time in vivo, deteriorating the tumor vessels and resulting in tumor embolism to cut the nutrient supply as well as causing cell death due to excessive lipid peroxidation. The RSL-3@PVs can also cause the classic ferroptosis-related change of mitochondrial morphology, with changes in cellular redox levels. Besides that, RSL-3@PVs has been proved to have great biological safety profile in vitro and in vivo. This study demonstrates the promising potential of integrating PVs and RSL-3 as a combination therapy for improving the outcome of PDAC.